Pengembangan Media Pembelajaran Flashcard dan Papan Braille untuk Mengenalkan Konsep Huruf Hijaiyah pada Disabilitas Netra di Kediri - Lestari, Sri; Ifriqia, Fartika; Rahmawati, Novi Rosita (Jurnal Pendidikan Kebutuhan Khusus, 2025)
This study develops innovative learning media to introduce Hijaiyah letters to visually impaired students, addressing the lack of practical tools. The research aims to design and assess the feasibility of flashcards and a Braille board as instructional media. The study employs Research and Development (RnD) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection methods include validation questionnaires, response questionnaires, interviews, observations, and documentation. The findings reveal that: (1) The Braille Hijaiyah flashcards are designed using small impraboard cards, while the Braille board is made from plywood, with raised Braille text created using thumbtacks to suit students' needs. (2) Feasibility tests by media and subject matter experts confirm its high validity. The media expert's validation score is 3.8, and the subject matter expert's score is 3.87, both categorized as highly feasible. In conclusion, the Hijaiyah flashcard and Braille board learning media are highly valid and ready for use without revisions, offering an effective solution for visually impaired students to recognize Hijaiyah letters.